Through Archives, Images and Collaborations: Tomate Colectivo - Gonzales Oviedo, Julio César (2024)
The essay proposes an approach to the audiovisual practices of the popular communication group Tomate Colectivo. Based on the experience of the audiovisual series Trazando resistencias (tomatecolectivo, 2014a, 2014b, 2014c, 2014d, 2014e, 2014f, 2014g y 2014h), it invites us to question visuality as a field in tension that involves the production, distribution and cultural meanings of images in audiovisual practices in contexts of ecoterritorial struggles. In this way, an attempt is made to investigate the relevance of the collective’s digital audiovisual archives as a potential space for research and construction of narratives, which not only document social and cultural processes, but also construct countervisualities from the ecoterritorial struggles in Cajamarca, Peru.